The Ghosts of Sigmaringen - Phillip Watts (Studies in 20th & 21st Century Literature, 1999)
There seem to be two ways to write about Sigmaringen, the German town where an incapacitated Vichy government landed in September 1944…
Keywords: Sigmaringen; Ghost; Germany; German; Vichy government; 1944